Effect of harvesting method and package type on quality and shelf-life of mango fruits - Elzubeir, Mohamed; Abu-Goukh, Abu-Bakr; Adam, Osman Adam Osman (Gezira Journal of Agricultural Science; Vol 13 No 2 (2015), 2015)
The traditional method of harvest and package type were compared with an improved harvesting technique and packaging in standard export carton boxes and evaluated according to quality and shelf-life of 'Kitchner' and 'Abu-Samaka' mango fruits in 'Abu-Gebeha' area during 2012/2013 season. The fruits harvested by the traditional method were snapped by a hook attached to a long bamboo pole, the fruits dropped to the ground and then picked into carton boxes. In the improved method of harvest, the fruits were picked by a hook attached to a long bamboo pole equipped with a long cloth sleeve held open by a metal ring. When the pedicle was severed, the fruit dropped into the sleeve, moved smoothly downwards to be received from the open-end by the picker and packed into the carton boxes. Two types of packages were used. The traditional packages were carton boxes 27 x 27 x 42cm, and the improved packages were standard export boxes 43 x 33 x 15 cm. The treatments were (1) traditional harvest and traditional packages (control), (2) traditional harvest and improved packages, and (3) improved harvest and improved packages. The treatments were arranged in a completely randomized design with four replicates and stored at 18±1 o C and 85- 90% relative humidity. The improved method of harvest and improved packages significantly delayed the onset of the climacteric peak, reduced respiration rate, weight loss, fruit softening, peel color development, total soluble solids (TSS) accumulation and titratable acidity changes, retained ascorbic acid, maintained fruit quality and extended the shelf-life of mango fruits. Initial respiration rate was decreased by 14.9% and 24.6%, weight loss was reduced by 13.8% and 28.9% and ascorbic acid was more by 28.6% and 75.5% in the improved harvesting method and improved packages, compared with the control in 'Kitchner' and 'Abu-Samaka' mangoes, تمت مقارنة طريقة الحصاد التقليدية ونوع العبوة المستخدمة مع طريقة محسنة للحصاد والتعبئة في صناديق الكرتون الخاصة بالصادر وتأثيرها على الجودة والعمر التسويقي لصنفي ثمار المانجو "كتشنر" و"أبو سمكة" في منطقة "أبو جبيهة". في طريقة الحصاد التقليدية، حصدت الثمار بنزعها بواسطة عصا طويلة في نهايتها خطاف مما يؤدى إلى سقوط الثمار على الأرض ويتم جمعها لاحقاً في حاويات الجمع. أما في الطريقة المحسنة، فقد أضيف إلى أداة القطف التقليدية كيس طويل من القماش مثبت على حلقة معدنية تحت الخطاف. عند فصل الثمرة من الغصن تسقط داخل الكيس وتنساب برفق إلى أسفل حيث يتم استلامها بواسطة عامل القطف من الفتحة السفلى للكيس وتوضع مباشرة في حاويات الجمع. كما أستخدم نوعان من العبوات: العبوات التقليدية كانت بأبعاد 27x27x42 سم، والعبوات المحسنة كانت صناديق الكرتون الخاصة بالصادر بأبعاد 43x33x15سم. وقد كانت المعاملات كما يلي: (1) حصاد تقليدي وعبوة تقليدية (الشاهد)، و(2) حصاد تقليدي وعبوة محسنة، و(3) حصاد محسن وعبوة محسنة. استخدم التصميم كامل العشوائية  لإجراء التجربة بأربعة مكررات وخزنت الثمار تحت درجة حرارة 18±1ºم ورطوبة نسبية 85 - 90 %.  أدت طريقة الحصاد المحسنة والعبوات المحسنة إلى تأخير معنوي في حدوث ذروة التنفس وانخفاض معدل التنفس، وفقدان الوزن، وليونة الثمرة وتلون قشرتها، وتأخير تراكم المواد الصلبة الذائبة الكلية وخفض معدل الحموضة في الثمار. كما حافظت الثمار على محتواها من حمض الأسكوربيك (فايتامين ج)، وتحسين جودتها، و إطالة عمرها التسويقي. وقد انخفض معدل التنفس الابتدائي بنسبة 14.9% و24.6%، كما انخفض فقد الوزن بنسبة 13.8% و28.9%، وكان حمض الأسكوربيك أكثر بمقدار 28.6% و75.5% بطريقة الحصاد المحسنة والعبوات المحسنة في ثمار "كتشنر" و"أبوسمكة"، على التوالي، مقارنة مع الشاهد. بنهاية فترة التخزين، كانت48% من الثمار في درجة الجودة "جيد جداً" و22% في درجة "جيد" في الثمار التي حصدت بالطريقة المحسنة وتمت تعبئتها في العبوات المحسنة، مقارنة مع 18.5 % من الثمار في درجة "جيد جداً" و20% في درجة "جيد" في الثمار التي تم حصادها بالطريقة التقليدية وتعبئتها في عبوات تقليدية. من ناحية أخرى، لم يكن هناك سوى 9.0% من الثمار "غير القابلة للتسويق" و9.5% "فقيرة في الجودة" في الثمار التي حصدت بالطريقة المحسنة وتم تعبئتها في عبوات محسنة، مقارنة بنسبة 25% من الثمار "غير القابلة للتسويق" و20% من الثمار "فقيرة في الجودة" في ثمار الشاهد.